2015
DOI: 10.1155/2015/747816
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T Lymphocyte-Associated Antigen 4 Gene Polymorphisms and Autoimmune Thyroid Diseases: An Updated Systematic Review and Cumulative Meta-Analysis

Abstract: The association of the cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) gene and susceptibility to autoimmune thyroid diseases (AITDs) has been studied extensively. However, the results were not the same in different ethnic groups. We updated the meta-analysis of association of CTLA-4 gene polymorphisms with AITDs and summarized the results in specific ethnicity. The associations of A49G gene polymorphism with GD, A49G gene polymorphism with HT, CT60 gene polymorphism with GD, and CT60 gene polymorphism wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
(16 reference statements)
0
12
0
2
Order By: Relevance
“…However, we have tested the Norwegian cohort in this study and in a pilot subgroup of British AAD patients for autoantibodies against 21-OH, a positive marker for an ongoing autoimmune condition against the adrenals, and found similar results (data not shown). Deviations of results in different populations have also been reported for CTLA-4 associations with, for example, type 1 diabetes and autoimmune thyroid diseases (reviewed in Hou et al 29 and Wang et al 30 ). Notably, however, when the data indicate an association, it is most often with the same allele (for example, the G-allele concerning rs231775).…”
Section: Discussionmentioning
confidence: 92%
“…However, we have tested the Norwegian cohort in this study and in a pilot subgroup of British AAD patients for autoantibodies against 21-OH, a positive marker for an ongoing autoimmune condition against the adrenals, and found similar results (data not shown). Deviations of results in different populations have also been reported for CTLA-4 associations with, for example, type 1 diabetes and autoimmune thyroid diseases (reviewed in Hou et al 29 and Wang et al 30 ). Notably, however, when the data indicate an association, it is most often with the same allele (for example, the G-allele concerning rs231775).…”
Section: Discussionmentioning
confidence: 92%
“… 115 120 CTLA-4 and its gene polymorphisms are reported to be important genetic determinants of the risk of T1DM and/or AITD. 43 , 96 , 121 134 …”
Section: Genetics and Autoimmunitymentioning
confidence: 99%
“…Recent series of meta-analysis pointed out, that CTLA-4 locus is rather general autoimmune than disease-specific genetic risk factor, especially the exon 1 and 3'UTR located markers, while their association with diseases susceptibility depends on the ethnicity. For example, it was shown that CTLA-4c.49A>G[G] and CT60 [G] alleles are risk factors, especially in Caucasians or Asians, for: autoimmune thyroid diseases [33], autoimmune adrenal insufficiency [34], type 1 diabetes [35], rheumatoid arthritis [36] and systemic lupus erythematosus [37,38]. The only association between CTLA-4g.319C>T and autoimmune disease susceptibility was observed for SLE in Asians [38].…”
Section: Discussionmentioning
confidence: 99%